2018
DOI: 10.1080/14616696.2018.1494293
|View full text |Cite
|
Sign up to set email alerts
|

Online discontent: comparing Western European far-right groups on Facebook

Abstract: Far-right groups increasingly use social media to interact with other groups and reach their followers. Social media also enable 'ordinary' people to participate in online discussions and shape political discourse. This study compares the networks and discourses of Facebook pages of Western European far-right parties, movements and communities. Network analyses of pages indicate that the form of far-right mobilization is shaped by political opportunities. The absence of a strong far-right party offline seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…Third, the sample is focused on an Anglophone context and these findings do not necessarily apply to other language communities. However given similar frames of nativism and anti-liberalism in global far right communication, white thymos can be expected to be observed in other contexts, though its relative salience and specific flows are likely to be different (see Caiani and Kröll 2015, Moffitt 2017, Froio 2018, Froio and Ganesh 2019, Klein and Muis 2019.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the sample is focused on an Anglophone context and these findings do not necessarily apply to other language communities. However given similar frames of nativism and anti-liberalism in global far right communication, white thymos can be expected to be observed in other contexts, though its relative salience and specific flows are likely to be different (see Caiani and Kröll 2015, Moffitt 2017, Froio 2018, Froio and Ganesh 2019, Klein and Muis 2019.…”
Section: Resultsmentioning
confidence: 99%
“…This right is only attributed to particular people, based on their identity. Comparing comments on Facebook pages of right-wing parties and non-institutional groups across four European countries, Klein and Muis (2019) showed that on non-institutional pages such as the one of the GIM, anti-immigration, and anti-Islam issues were discussed frequently. Caiani and Kröll (2017) included the GIM's website and blog in their analysis of the relationship between populist (people vs. elites) and nationalist (ethno-national people vs. others) frames.…”
Section: This Study: Strategic Frames In Memesmentioning
confidence: 99%
“…We take an approach that draws on research into the social construction of imaginaries of Europe. Similar to recent work by Klein and Muis (2019) and using methods in corpusaided discourse analysis (Bayley and Williams 2012), we focus on collocations of the word Europe in tweets. Specifically, for each language, we collect all instances of the word Europe for the seed and the audience.…”
Section: Methodsmentioning
confidence: 99%